Does forestry public-private partnership promote the development of China’s forestry economy? - Yang, Chuwei; Shang, Hangbiao (Frontiers in Environmental Science, 2023)
In 2016, China began to introduce the public-private partnership (PPP) model in forestry to explore the promotion and modern development of the nation's forestry industry. Based on the New Governance Theory, this study explores whether PPP, as an essential investment and financing model, can impact China's forestry economy. Based on provincial-level panel data from 2011 to 2020 in China, this study examines the effects of PPP on China's forestry economy using the difference-in-differences (DID) model. This study tests the robustness of the effects using a multi-stage propensity score matching-DID model and explores the mechanism of the effect. The relevant results are threefold. (1) PPP in forestry can significantly enhance China's forestry economy. (2) PPP in forestry can enhance the forestry economy through industrial structure and technological innovation effects. (3) Although forestry PPP has effectively promoted economic growth in forestry, the initial implementation process will have a negative ecological impact. This study provides a scientific basis for promoting forestry PPP and improving China's forestry economy's high-quality and sustainable development.